The Effect of the Collaborative Learning Model on the Mathematical Problem-Solving Ability of Grade VIII Students at SMPN 1 Sasak Ranah Pesisir in the 2023/2024 Academic Year - Andrayani, Anisa; Haida Fitri; Rusdi; M. Imamuddin (The Future of Education Journal, 2025)
This study was motivated by a problem identified in Grade VIII at SMPN 1 Sasak Ranah Pesisir, where students demonstrated low mathematical problem-solving abilities. This issue is suspected to have caused many students to perform below the minimum competency criteria in problem-solving. To address this issue, the researcher implemented the Collaborative Learning model in mathematics instruction, which is believed to enhance students’ problem-solving skills. The research question posed was: Does the Collaborative Learning model have a greater impact on students' mathematical problem-solving abilities compared to conventional learning among Grade VIII students at SMPN 1 Sasak Ranah Pesisir? This study used a pre-experimental method with a static group comparison design. The population consisted of all eighth-grade students at SMPN 1 Sasak Ranah Pesisir. The sample was selected randomly after conducting normality and homogeneity tests on the population data. Class VIII.4 was designated as the experimental group, and Class VIII.2 as the control group. The instrument used in this study was an observation sheet and a test on students' mathematical problem-solving abilities. Data were analyzed using hypothesis testing with the t-test formula. The results showed that the calculated t-value (tₕ = 2.290) was greater than the critical t-value (tₜ = 1.673), leading to the rejection of the null hypothesis (H₀). Using SPSS software at a significance level of α = 0.05, the p-value was 0.026, which is less than α, confirming that H₀ was also rejected. Thus, it can be concluded that the Collaborative Learning model positively affects students’ mathematical problem-solving abilities, showing higher results compared to those taught using conventional methods in Grade VIII at SMPN 1 Sasak Ranah Pesisir in the 2023/2024 academic year.